2015
DOI: 10.1002/hbm.23014
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale brain network abnormalities in Huntington's disease revealed by structural covariance

Abstract: Huntington's disease (HD) is a progressive neurodegenerative disorder that can be diagnosed with certainty decades before symptom onset. Studies using structural MRI have identified grey matter (GM) loss predominantly in the striatum, but also involving various cortical areas. So far, voxel-based morphometric studies have examined each brain region in isolation and are thus unable to assess the changes in the interrelation of brain regions. Here, we examined the structural covariance in GM volumes in pre-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 62 publications
(95 reference statements)
1
13
0
Order By: Relevance
“…Structural covariance network analysis provides another angle of brain network change by examining the inter‐regional co‐variation of brain volume across the population . Altered patterns of structural covariance have been found in many brain disorders, such as AD, schizophrenia, epilepsy and autism but to a lesser extent in Huntington disease . We found that Huntington disease greatly reduced the structural covariance in almost all the networks and memantine treatment ameliorated this reduction.…”
Section: Discussionmentioning
confidence: 64%
“…Structural covariance network analysis provides another angle of brain network change by examining the inter‐regional co‐variation of brain volume across the population . Altered patterns of structural covariance have been found in many brain disorders, such as AD, schizophrenia, epilepsy and autism but to a lesser extent in Huntington disease . We found that Huntington disease greatly reduced the structural covariance in almost all the networks and memantine treatment ameliorated this reduction.…”
Section: Discussionmentioning
confidence: 64%
“…Here, in all pre-specified motor, working memory, cognitive flexibility, and social-affective networks there were no differences between controls and pre-HD observed (Minkova et al, 2016). In our study, however, we found evidence for early grey matter volume changes in two structural covariance networks in pre-HD compared to controls.…”
Section: Discussionmentioning
confidence: 81%
“…In HD, network-based analysis has been applied in one other recent study that investigated structural covariance networks in brain regions that are functionally related (Minkova et al, 2016). Here, in all pre-specified motor, working memory, cognitive flexibility, and social-affective networks there were no differences between controls and pre-HD observed (Minkova et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating research demonstrates that lifespan changes to brain structures do not occur independently but follow multi-regional, coherent patterns that show unique chronological trajectories of integrity and organization (Alexander-Bloch et al, 2013;Li, Pu, Fan, Niu, Li, & Li, 2013;V a sa et al, 2017;Zhu et al, 2012;Zielinski, Gennatas, Zhou, & Seeley, 2010). SCov has proven to be a sensitive method in studying disease, and alterations exist in a range of disorders that are neurodegenerative (Coppen, van der Grond, Hafkemeijer, Rombouts, & Roos, 2016;Minkova et al, 2016), psychiatric (Palaniyappan et al, 2015;Wu et al, 2017;Xu, Groth, Pearlson, Schretlen, & Calhoun, 2009), developmental (Bethlehem, Romero-Garcia, Mak, Bullmore, & Baron-Cohen, 2017;Dziobek, Bahnemann, Convit, & Heekeren, 2010), systemic (e.g., cardiovascular risk factors) (Kharabian Masouleh et al, 2017), and even chemotherapy-related (i.e., cognitive impairment) (Hosseini, Koovakkattu, & Kesler, 2012). A seed-to-whole-brain and seed-to-target transdiagnostic SCov application using BrainMap VBM was recently published by Kotkowski, Price, Mickle Fox, Vanasse, and Fox (2018).…”
mentioning
confidence: 99%